2019
DOI: 10.3389/fchem.2018.00630
|View full text |Cite
|
Sign up to set email alerts
|

The Challenging in silico Description of Carbon Monoxide Oxidation as Catalyzed by Molybdenum-Copper CO Dehydrogenase

Abstract: Carbon monoxide (CO) is a highly toxic gas to many living organisms. However, some microorganisms are able to use this molecule as the sole source of carbon and energy. Soil bacteria such as the aerobic Oligotropha carboxidovorans are responsible for the annual removal of about 2x108 tons of CO from the atmosphere. Detoxification through oxidation of CO to CO2 is enabled by the MoCu-dependent CO-dehydrogenase enzyme (MoCu-CODH) which—differently from other enzyme classes with similar function—retains its catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In this work, we present for the first time a reaction mechanism for the oxidation of CO to CO 2 catalyzed by the Mo/Cu-CODH enzyme that agrees with experimental data, in which dissociation of carbon dioxide takes place directly from the product of the nucleophilic attack reaction aided by the temporary coordination of the glutamate residue to the Mo ion and in which the formation of the thiocarbonate intermediate does not constitute a complication for the enzymatic process. This was achieved thanks to the experience gained by previous works that have shown that the computational modeling of this system requires special care. In particular, accurate modeling of the protein surrounding the active site, the employment of dispersion corrections, and sufficiently large basis sets in the description of the system proved to be crucial for achieving consistent results. Moreover, we employed the BigQM approach , to obtain refined energies of each step in the CO-oxidation catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we present for the first time a reaction mechanism for the oxidation of CO to CO 2 catalyzed by the Mo/Cu-CODH enzyme that agrees with experimental data, in which dissociation of carbon dioxide takes place directly from the product of the nucleophilic attack reaction aided by the temporary coordination of the glutamate residue to the Mo ion and in which the formation of the thiocarbonate intermediate does not constitute a complication for the enzymatic process. This was achieved thanks to the experience gained by previous works that have shown that the computational modeling of this system requires special care. In particular, accurate modeling of the protein surrounding the active site, the employment of dispersion corrections, and sufficiently large basis sets in the description of the system proved to be crucial for achieving consistent results. Moreover, we employed the BigQM approach , to obtain refined energies of each step in the CO-oxidation catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…The structural motifs that appear to have an effect on the reactivity are (i) coordination of Mo­(VI) by a redox-active dithiolene ligand that stabilizes the formally Mo­(VI) oxidation state, (ii) several ligands multiply bonded to Mo­(VI), which increases the nucleophilic character of the reactive oxo by decreasing the metal–oxo bond order, , (iii) coordinative unsaturation at the Cu­(I) site, consistent with substrate (CO) coordination, , and (iv) the proximity of Mo­(VI) and Cu­(I), enabled by the sulfido bridge. The mechanism of CO oxidation was probed by spectroscopic and computational studies. One of the leading current mechanistic hypotheses, supported by DFT calculations, suggests that the initial binding of CO to Cu­(I) ( I -CO) is followed by a nucleophilic attack of Mo-oxo on the electrophilic carbon of CO to form intermediate II . The subsequent oxidation of carbon and reduction of Mo (formally oxo transfer) results in the formation of intermediate III , which is reoxidized to I .…”
Section: Introductionmentioning
confidence: 99%
“…coli was found to be a suitable host for the expression of Mo–Cu CODH after the discovery of a molybdopterin-cytosine-dinucleotide-type (MCD-type) Mo cofactor . This MCD-type Mo cofactor is very unique, exclusive, and pivotal to establish the catalytic activity of expressed recombinant Mo–Cu CODH. ,, …”
mentioning
confidence: 99%
“…However, its practical applications have been largely hampered by the extreme sensitivities of these prolific CO oxidizing enzymes to oxygen, leading to its inactivation in CO oxidation activity. In contrast, Mo−Cu CODH has a rare and special feature in which it retains its catalytic activity regardless of oxygen presence (or absence), 3 hence opening an opportunity for Mo−Cu CODH to be prospectively used for an application such as a CO sensor catalytic unit.…”
mentioning
confidence: 99%
See 1 more Smart Citation